Analysis Of Merchandise Inventory Control Using Eoq, Rop, Ss Methods At Raffa Bengkulu Fruit Store - Yusni Octavia Batu Bara; Ida Anggriani; Herlin Herlin (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
Raffa's Fruit Shop Business is a shop that distributes merchandise which operates in the fruit sector. Among the various methods available, the methods used are the EOQ, ROP, and Safety Stock methods. This research aims to analyze fruit inventory control using the EOQ, ROP, SS method at the Raffa Fruit Shop, Bengkulu City. The data analysis used is descriptive qualitative, namely a research method to determine variable values ​​without making comparisons. The results of this research show that the required quantity of merchandise for 1 period is 671,159 Kg, the economical purchase amount or EOQ is 24,291 Kg, the Purchase Frequency is 28 orders. Reorder Point or reorder point is 40,197 Kg, and Safety Stock or safety stock is 392.81 Kg.